2022
DOI: 10.1093/ckj/sfac055
|View full text |Cite
|
Sign up to set email alerts
|

Wasp stings and plasma exchange

Abstract: Invasive species related to climate change and/or globalization may be associated with novel forms of kidney disease. This is the case for wasps. Several species of Asian wasps are increasingly found in America (e.g. Asian giant hornet, Vespa mandarinia) and Europe (e.g. yellow-legged Asian hornet, V. velutina; black shield hornet; V. bicolor and Oriental hornet, V. orientalis). Some of these species have been associated with human deaths and acute kidney injury. The literature on wasps and acute kidney injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…[ 79 ] found that TPE treatment significantly decreases the mortality rate of wasp sting patients compared with those not treated with TPE; however, CRRT and hemoperfusion did not significantly reduce mortality [ 79 ]. According to these results, the TPE + CRRT combination appears to be a more suitable therapy option for wasp venom-induced AKI [ 11 , 79 ]. Nevertheless, doctors and nurses should be aware of the adverse events of TPE, such as hemorrhage, particularly in the case of wasp sting patients with abnormal coagulation.…”
Section: Therapeutic Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 79 ] found that TPE treatment significantly decreases the mortality rate of wasp sting patients compared with those not treated with TPE; however, CRRT and hemoperfusion did not significantly reduce mortality [ 79 ]. According to these results, the TPE + CRRT combination appears to be a more suitable therapy option for wasp venom-induced AKI [ 11 , 79 ]. Nevertheless, doctors and nurses should be aware of the adverse events of TPE, such as hemorrhage, particularly in the case of wasp sting patients with abnormal coagulation.…”
Section: Therapeutic Measuresmentioning
confidence: 99%
“…Another study indicated that wasp stings generally inflict more severe outcomes than bee stings [ 10 ]. The progression of wasp venom-induced AKI is rapid and delayed admission is an independent risk factor for AKI following a wasp sting [ 11 , 12 ], which can seriously impact clinical progress. In a retrospective cohort study of 112 patients with wasp stings, no patients without AKI died [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation